1995
DOI: 10.1074/jbc.270.34.19723
|View full text |Cite
|
Sign up to set email alerts
|

Identity of the Segment of Human Complement C8 Recognized by Complement Regulatory Protein CD59

Abstract: CD59 antigen is a membrane glycoprotein that inhibits the activity of the C5b-9 membrane attack complex (MAC), thereby protecting human cells from lysis by human complement. The inhibitory function of CD59 derives from its capacity to interact with both the C8 and C9 components of MAC, preventing assembly of membrane-inserted C9 polymer. MAC-inhibitory activity of CD59 is species-selective and is most effective when both C8 and C9 derive from human or other primate plasma. Rabbit C8 and C9, which can substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 21 publications
1
44
1
Order By: Relevance
“…MAC formation itself is regulated through interaction with CD59, a widely distributed, membrane-anchored glycoprotein that binds to C8␣ and C9 and thereby restricts MAC assembly and function. Earlier studies showed the CD59-binding site in C8␣ is within a segment defined by residues 334 -385 in TMH2 (52). More recently, it was suggested the binding site lies within residues 350 -355 (53).…”
Section: Discussionmentioning
confidence: 99%
“…MAC formation itself is regulated through interaction with CD59, a widely distributed, membrane-anchored glycoprotein that binds to C8␣ and C9 and thereby restricts MAC assembly and function. Earlier studies showed the CD59-binding site in C8␣ is within a segment defined by residues 334 -385 in TMH2 (52). More recently, it was suggested the binding site lies within residues 350 -355 (53).…”
Section: Discussionmentioning
confidence: 99%
“…Human CD59 is an 18-kDa glycosylphosphatidylinositollinked membrane glycoprotein, widely expressed in all circulating cells and most tissues, that serves as an inhibitor of the C5b-9 MAC of human complement (9,17,39,48). The complement inhibitory activity of CD59 depends on its ability to bind to C8 in the C5b-8 complex (30) and to C9 between Cys359 and Cys384 (21), thereby inhibiting ion channel formation by C5b-8 (13) and generation of the polymerized C9 responsible for MAC cytolytic activity (36,39,48). In contrast to CD59 that binds to C8␣ (30), paramyosin appears to bind both C8␣ and C8␤ chains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CD59 is an 18-kDa membrane glycoprotein expressed in most vertebrate tissues (9,10) that protects homologous cells from damage by complement. It binds to C8 and C9 (30,39) and inhibits assembly of the C5b-9n membrane attack complex (MAC) (36,48). As described here, sequencing and specific antibody binding data indicate that SCIP-1 is a tegumental form of paramyosin.…”
mentioning
confidence: 99%
“…Based on the solved solution structure of CD59, these data suggest that selectivity for human C8 and C9 resides in a cluster of closely spaced side chains on the surface of CD59 contributed by His 44 CD59 is a 77-residue glycosylphosphatidylinositol (GPI) 1 anchored plasma membrane glycoprotein that serves to protect human blood and vascular cells from injury by the C5b-9 components of the complement system present in plasma (1)(2)(3)(4)(5)(6). The complement inhibitory function of CD59 resides in its capacity to interrupt formation of lytic pores in the plasma membrane by binding to segments of the C8␣ and C9 polypeptides that become exposed during their assembly into the complement C5b-9 membrane attack complex (MAC) (7)(8)(9)(10)(11)(12)(13). The amino acid sequence and solution structure of CD59 conform to those of the Ly6/cardiotoxin protein superfamily in which five internal disulfide bonds stabilize the polypeptide into a discoid structure consisting of a three-stranded ␤-sheet apposed to a two-stranded ␤-finger (14 -17).…”
mentioning
confidence: 99%
“…This implies that the CD59 homologue expressed on the surface of rabbit cells is also selective for homologous complement and cannot effectively interact with the human C8 and C9 components to inhibit MAC. We have previously taken advantage of the species selectivity inherent to the interaction of CD59 with C8 and C9 to map the peptide-binding sites within the human C8 and C9 proteins that are recognized by human CD59 (7,8,26). In those studies, the capacity of human CD59 to inhibit MAC assembly was measured using recombinant human/rabbit chimeras of C8 and C9 in order to identify the residues within the C8␣ and C9 polypeptides that are specifically required to confer recognition of these complement components by human CD59.…”
mentioning
confidence: 99%